2012
DOI: 10.4103/1463-1741.104897
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental noise on sleep

Abstract: This paper summarizes the findings from the past 3 year's research on the effects of environmental noise on sleep and identifies key future research goals. The past 3 years have seen continued interest in both short term effects of noise on sleep (arousals, awakenings), as well as epidemiological studies focusing on long term health impacts of nocturnal noise exposure. This research corroborated findings that noise events induce arousals at relatively low exposure levels, and independent of the noise source (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(90 citation statements)
references
References 25 publications
1
84
0
5
Order By: Relevance
“…It is a common cause of various types of psychosocial and health-related impairments (9)(10)(11)(12). In Europe, road traffic noise constitutes the dominant source of noise annoyance (13).…”
mentioning
confidence: 99%
“…It is a common cause of various types of psychosocial and health-related impairments (9)(10)(11)(12). In Europe, road traffic noise constitutes the dominant source of noise annoyance (13).…”
mentioning
confidence: 99%
“…Due to the very low background sound levels at most locations we conducted an additional C-weighted analysis of the background to peak noise ratios. The observed ratios at all locations were very high for an urban area ( Figure 7) and can result in relevant autonomous cardiovascular reactions during sleep [38,52,56]. The analysis indicated also a clear difference between "old" and "new" trams ( Figure 6), which was not distinguishable with the A-weighted approach and further supports not to use A-weighting for this environmental health risk assessment.…”
Section: Discussionmentioning
confidence: 74%
“…Typically, the overall traffic noise decreases and silence is interrupted by passing trams, especially in quieter suburban areas. In addition, sleep research has found these socalled shoulder hours (10:00 p.m. to 12:00 p.m. and 5:00 a.m. to 7:00 a.m.) to be sensitive times for noise exposure and subsequent interference with the sleep and restoration process [38][39][40]. Eventually, noise and vibrations show potential for mutual interactive effects on annoyance and sleep disturbance [24,[41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Získava si však stále väčšiu pozornosť, pretože je považovaný za najnepríjemnejší a najrušivejší hluk, a práve preto je najčastejšie uvádzaným dôvodom proti rozširovaniu letísk. V roku 2006, bola svetová populácia vystavená leteckému hluku s 55 L dn a očakáva-me nárast vo výške 0,7 až 1,6 % ročne (9).…”
Section: Hluk V žIvotnom Prostredíunclassified